The Contagion Effect of Muslim Street Rallies on Stocks’ Volatility: Is it a Political Risk for Investors? - Wiwiek Rabiatul Adawiyah; Bambang Agus Pramuka (Jurnal Keuangan dan Perbankan, 2018)
Muslim street rallies refer to the super-peaceful mass street mobilizations to pressure law enforcement against a blasphemer, the Governor of Jakarta. The Event was organized by the National Movement to Safeguard the Indonesian Muslim Scholar Council’s Fatwa (GNPF-MUI) on the 4th of November (411) and 2nd of December (212) 2016 at the capital city of Indonesia. We compare the performance of stock returns and shares trading volume on the Indonesian Stock Exchange (IDX) before and after the events. The observations were made stock performance seven days before and after the events. We found that the event had a significant influence on the abnormal return of stocks sold in the Indonesian Stock Exchange during the first event held on November 4th, but the case was different on the second event. Thus, investors do not consider the event as a political risk for portfolio investment. This study contributes to existing literature as the first to analyze the impact of the super peaceful rally on the pattern of stock price and trading volume in the Indonesian stock market.JEL Classification: G14, G32DOI: https://doi.org/10.26905/jkdp.v22i4.2123